Only one place of redress : African Americans, labor regulations, and the courts from Reconstruction to the New Deal - Bernstein, David E. (Constitutional conflicts., 2001)
Focuses on the role facially-neutral labor regulations played in institutionalizing discrimination against African Americans in the period between Reconstruction and the civil rights era.